A Prevalence of Thyroid Disorders at Al-Wahat Region of Libya During 2022 - Matter , Hamdy AB.; Ayad , Tariq M; Nofal , Yasser; Inwajy , Ali (Scientific Journal of University of Benghazi, 2023)
About 1272 cases of thyroid hormones were examined. The study was conducted during the year 2022 in the Al-Wahat region / Libya, it was found that 10.5% suffer from a disorder in their hormones, 40% of these cases suffer from a deficiency in their hormones, and 60% of them suffer from an excess. The number of women who suffer from a disorder in their hormones was 81%, while the number of men was 19%, 48% of women with high, and those with low was 33%. In addition, 13% of the males with high and those with low was 6%. It was found that the high and low % increase as the normal distribution from the age of 30 to 70 for all cases of thyroid gland disorder with a mean of 44 years and a standard deviation S = 17.5 for high values, and 18.9 for low values. The variation coefficient of 39.7 and 42.9, and the most common age was (The mode) for the high is 40 years and for the low is 30 years. In other words, the high is greater than the low for them, and the mean in both cases is the age of 40. The most common values for the high are at 42 in general, while in low they have about 37 years, and the median in high is about 45 years, while in low is about 30 years. The high is higher for males than the low and the mean for high is 49 years, while for low is 60 years, and S = 20.2 for high and S = 27.7 for low, and there is no correlation between high or low between men and women as indicated by the measurement of Pearson's correlation coefficient.